Cysticercosis breast - a rare entity. - Paras, KP; Nikhil, M; Ashwani, K; Anshul, S; Reetinder, C; Pankaj, G; Ashish, K (Department of Surgery, UKM Medical Centre, 2013)
It is unusual for cysticercosis to occur in the substance of the breast. Diagnosis is usually made incidentally. Only few cases are described in the literature. We here report a case of cysticercosis perched on fibroadenoma of breast found on surgical excision in a 16-year-old unmarried female patient. The patient had no discernible evidence of cysticercosis in the other organs. Surgical excision was performed and histological examination demonstrated the presence of cysticercus cellulosae larvae. Characteristic features of this uncommon location are discussed based on a review of the literature. Thus the possibility of cysticercosis of the breast should be kept in mind while considering the differential diagnosis for a breast lump.